A case-control study of the aetiology of cryptorchidism. Issue 3 (September 1983) - Swerdlow, A J; Wood, K H; Smith, P G
Abstract : A study of cryptorchidism was undertaken based on patients identified through the Oxford Record Linkage Study. The cumulative lifetime incidence of archidopexy among males in the study area was estimated to be 3.38%; 88% of orchidopexies were performed on males aged 5 years and over and 32% on those aged 10 and over. In a case-control study with 146 cases ascertained at orchidopexy and 146 matched controls there was a substantially increased risk of cryptorchidism for those who had undergone breech labour. Raised risks of cryptorchidism were found for boys born to mothers who were primigravidas or aged under 20, and a significantly reduced risk was found for boys whose mothers were of B blood group. There was a gradient of increasing risk with decreasing birth weight and a significantly raised risk associated with clinical inguinal hernia. Since cryptorchidism and testicular cancer share several risk factors, it may be profitable to study newly identified risk factors for cryptorchidism in relation to testicular cancer.